2002
DOI: 10.1182/blood.v99.10.3566
|View full text |Cite
|
Sign up to set email alerts
|

In vivo depletion of hematopoietic stem cells in the rat by an anti-CD45 (RT7) antibody

Abstract: Anti-CD45 monoclonal antibodies (mAbs) are potentially powerful tools for the depletion of mature leukocytes. As their application for immunotherapy also depends on their effects on bone marrow (BM) progeny, the in vivo effects of an anti-CD45 mAb (anti-RT7 a mAb) on BM precursor cells were analyzed in a rat model. Anti-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
(25 reference statements)
1
19
0
Order By: Relevance
“…The difference in expression rates of CD49f (integrin ·6) and Á‰TCR was marginal and no difference was noted in the expression rates of CD90 (Thy-1), CD34 and CD29 (integrin ß1) between the two fractions. Substantial expression of CD45 is known to be observed in virtually all committed hematopoietic cells (25,26). When the cells were analyzed after double immunolabeling, positive cells in the expression of CD117 or CD200 were found solely in the CD45-positive populations (Fig.…”
Section: Expression Of Marker Proteins In the Cells Recovered In Mnc mentioning
confidence: 93%
“…The difference in expression rates of CD49f (integrin ·6) and Á‰TCR was marginal and no difference was noted in the expression rates of CD90 (Thy-1), CD34 and CD29 (integrin ß1) between the two fractions. Substantial expression of CD45 is known to be observed in virtually all committed hematopoietic cells (25,26). When the cells were analyzed after double immunolabeling, positive cells in the expression of CD117 or CD200 were found solely in the CD45-positive populations (Fig.…”
Section: Expression Of Marker Proteins In the Cells Recovered In Mnc mentioning
confidence: 93%
“…An alternative, potentially more specific and thus less toxic approach to conditioning is the use of monoclonal antibodies directed against stem cell antigens or more common leukocyte antigens. 173 Although it is likely that side effects associated with conditioning regimens will be reduced significantly in the near future, this issue will continue to be an important aspect of the risk-benefit evaluation for stem cell-based gene therapy.…”
Section: Risks Related To Conditioning Use Of Selective Drugs and Cmentioning
confidence: 99%
“…Results from a congenic stem-cell transplantation study in rats demonstrated that by using an isoform-specific anti-CD45 mAb treatment, a significant depletion of host stem cells could indeed be obtained. 25 However, further research is needed to address the efficiency of this approach.NK-cell function is coordinated by complex interactions between different inhibitory and activating receptors, 26,27 making it difficult to study the mechanism responsible for NK-cell tolerance. Preliminary data of Ly49A and Ly49D expression on host NK cells support the conclusion that the observed NK-cell nonresponsiveness was indeed the result of NK-cell tolerance.…”
mentioning
confidence: 99%
“…Results from a congenic stem-cell transplantation study in rats demonstrated that by using an isoform-specific anti-CD45 mAb treatment, a significant depletion of host stem cells could indeed be obtained. 25 However, further research is needed to address the efficiency of this approach.…”
mentioning
confidence: 99%